Collective Bargaining Alternative: A Case of Strategic Industrial Relations Initiative (Global Business Management Review (GBMR), 2022)
India’s Industrial relation scenario has been undergoing a paradigm shift. The role of trade unions is changing from firefighting to the business partner role. The trade unions need to align their activities with business goals in this changing scenario. For the trade unions, collective bargaining remained one of the oldest techniques for wage determination. With changing scenario, the usefulness and effectiveness of collective bargaining for the purpose of wage fixation is being questioned. This case has provided insights into a unique model of wage fixation, which was successfully implemented in the Biwadi Plant of Indian Tractor Limited (ITL)*. It highlights the challenges ITL faced in the process and the critical factors, which helped in successful implementation of the new model of wage fixation. Primary Data has been collected through in-depth interviews and focused group interviews with workers, trade unions members and management representatives. ITL is one of the rare examples where the company took up an unprecedented step by offering a proposal and working jointly with the union to make it happen, which we call as an alternative method of wage fixation.